The Effect of Rebranding on Purchase Intention Mediated by Brand Image and Perceived Quality: A Study of AZKO Consumers - Tiara Maharani Bulqis Yuwono; Nanang Suryadi; Himmiyatul Amanah Jiwa Juwita (Fundamental and Applied Management Journal, 2026)
Increasing competition in the retail industry and evolving consumer behavior have encouraged companies to adopt rebranding as an adaptive strategy to sustain competitiveness. The transformation from ACE Hardware to AZKO represents a significant case, particularly in understanding its impact on consumers’ purchase intention. However, changes in brand identity may create uncertainty in consumer perceptions, especially regarding brand image and perceived quality. Prior studies have also reported inconsistent findings on the direct effect of rebranding on purchase intention. This study aims to examine the effect of rebranding on purchase intention, with brand image and perceived quality acting as mediating variables. A quantitative approach was employed using a survey method targeting AZKO consumers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that rebranding has a positive and significant effect on brand image and perceived quality. Furthermore, rebranding influences purchase intention both directly and indirectly through these mediating variables. Brand image and perceived quality are proven to play significant mediating roles in strengthening the relationship between rebranding and purchase intention. These findings suggest that the success of rebranding is not solely determined by changes in visual or identity elements, but also by the company’s ability to build a positive brand image and enhance consumers’ perception of quality. This study contributes to the marketing literature by highlighting the mediating mechanisms within the rebranding framework and offers practical implications for companies in designing effective rebranding strategies to increase consumer purchase intention.